“Living on the Fat of the Faith”: On Founding an MFA at the University of Saint Thomas - Hren, Joshua (Christianity & literature, 2021)
This essay examines the need for new literature that makes attractive what we ought to worship even as it helps us “locate” ourselves amidst the continuum that swings from self-deceit to wisdom. It considers the ways in which a Catholic Christian Masters of Fine Arts (MFA) might make a distinctive contribution to these ends.